THE POSITION AND ROLE OF FINANCIAL SECURITY IN ENSURING THE ECONOMIC SECURITY OF RUSSIA - Vera V. Elizarova (Статистика и экономика, 2016)
The power and the national security of theState, as a guarantee of independence andsovereignty (both internal and external) ofthe State, the stability and efﬁciency of thelife of society, characterized by the ﬁ rst the State of its economy and protection fromthreats to ﬁnancial security. Financial securityin today’s environment plays a critical role in ensuring the economic security of the country. Economic security has traditionally been seen as an essential qualitative characteristicof the economic system, which determines itsability to maintain normal living conditions ofthe population, the sustainable provision ofresources for the development of the nationaleconomy, as well as consistent implementation of national interests.